PENGARUH PENERAPAN STRATEGI METAKOGNITIF TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA PEMBELAJARAN IPAS KELAS V GUGUS I SUDIRMAN SURAKARTA TAHUN AJARAN2024/2025 - Klara Yessa; Anggit Grahito; Jumanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students' thinking awareness in learning at school is not optimal because educators have not used appropriate strategies This study aims to determine the effect of applying metacognitive technique on students' cognitive them within the teaching and learning process fifth-grade science learning at SDN Gugus I Sudirman Surakarta, and to analyze the effectiveness of metacognitive strategies in increasing students' awareness and self-control of their learning process. This study employs a quasi-experimental design within a quantitative research framework One Group Posttest-Only Design with Nonequivalent. The research The study participants comprised 55 students, who were assigned to either an experimental group (n=27) or a control group (n=28). Data collection technique was through a A 20-item multiple-choice test that had been validated and tested for reliability was employed (0.739). Data were analyzed using normality, homogeneity, and an Independent Samples T-Test was conducted to compare the post-test results. The analysis revealed that the mean post-test score of the experimental group (78.15 was significantly higher than that of the control group (53.21). The research of the hypothesis test showed a t-test (2.964) > t-table (2.005) a significance level of 0.000 (p < .05) was found, which led to the conclusion that. The conclusion of this study is that metacognitive strategies have a significant and effective effect on improving students' cognitive learning outcomes in science learning.